WOMEN ISSUES IN TWO SHORT STORIES BY RATNA INDRASWARI IBRAHIM: A STUDY OF COMPARATIVE LITERATURE TOWARD TWO SHORT STORY; âRAMBUTNYA JUMINTENâ AND âBAJUâ - Mardani, Putri Bestari; Suprasti, Devi; Aratika, Juni (Universitas Muhammadiyah Surakarta, 2017)
Â TheÂ issueÂ ofÂ womenâsÂ lifeÂ hasÂ alwaysÂ beenÂ anÂ interestingÂ topicÂ toÂ be discussed. This kind of issue has been widely delivered by story writers, which is by placing women as the main character in his/her work. It aims to convey the results of their thoughts in the form of literary works. As already been known, literaryÂ worksÂ areÂ oneÂ ofÂ anÂ essentialÂ container Â toÂ describeÂ theÂ reflexivityÂ of society.Â SensitiveÂ issuesÂ couldÂ beÂ freelyÂ expressedÂ inÂ literaryÂ works.Â AsÂ an exampleÂ isÂ theÂ issueÂ ofÂ womenÂ whichÂ isÂ describedÂ inÂ shortÂ storiesÂ formÂ and published through the mass media.Â TheÂ aimsÂ ofÂ thisÂ paperÂ areÂ toÂ explainÂ theÂ formsÂ ofÂ problemsÂ orÂ issues revolving women that are presented in the âBajuâand âRambutnya Jumintenâtext by Ratna Indraswari Ibrahim. This study uses the theory of feminism by Simone de Beauvoir. Beauvoir suggests that women are considered as the second-class citizens or as the second sex due to patriarchal power, a notion that can lead to gender inequality (Kuntowijoyo 1987: 136).Â Based on the study, it was found that both texts reveal various forms of womenâs issues, which are patriarchy and gender constructions. Both traditional women and an empress with a high social position experience the same issue. Although the two female figures were trying to speak up, they are being ignored. This is because there is a widely known stereotype that states that women are emotional and irrational, so women are considered unable to manage their own lives and are not suitable to speak in a public sphere.Â Keyword:Â comparativeÂ literature,Â feminism,Â shortÂ story,Â RatnaÂ Indraswari, women issues.